2021
DOI: 10.1088/1361-6471/abde9b
|View full text |Cite
|
Sign up to set email alerts
|

Survey of texture zeros with light Dirac neutrinos

Abstract: We classify all possible texture zeros in a light neutrino mass matrix in a diagonal charged lepton basis by considering the Dirac nature of light neutrinos. For the Hermitian nature of neutrino mass matrix, the number of possible texture zeros remain the same as Majorana texture zeros, but with less free parameters due to the absence of additional Majorana CP phases. Relaxing the Hermitian nature of the neutrino mass matrix leads to many more possibilities and freedom due to additional CP phases, mixing angle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Several systematic studies of textures zeros in the leptonic sector can be found in the literature; see, for instance, refs. Borgohain & Borah (2021), Cebola et al (2015), Ludl & Grimus (2014). In any search for experimentally viable texture‐zero structures for fermion mass matrices, it is important to take into account the freedom to make weak basis transformations, which do not change the physical content.…”
Section: Theoretical Challengesmentioning
confidence: 99%
“…Several systematic studies of textures zeros in the leptonic sector can be found in the literature; see, for instance, refs. Borgohain & Borah (2021), Cebola et al (2015), Ludl & Grimus (2014). In any search for experimentally viable texture‐zero structures for fermion mass matrices, it is important to take into account the freedom to make weak basis transformations, which do not change the physical content.…”
Section: Theoretical Challengesmentioning
confidence: 99%
“…symmetric texture , and textures under discrete symmetries, for example, and [82]. The remainder of this paper is organized as follows: In Sec.…”
Section: Introductionmentioning
confidence: 99%
“…The neutrino mass matrix carries the information of all the physical parameters mentioned above and the theorists in general, try to predict a promising neutrino mass matrix starting from the first principle. Several phenomenological ideas such as µ − τ symmetry [5][6][7], texture zeroes [8,9], hybrid textures [10,11], vanishing minors [12,13] etc. are attributed to the neutrino mass matrix and are studied extensively from both bottom-up and top-down viewpoints.…”
mentioning
confidence: 99%